The evidence base of proton pump inhibitor chemopreventative agents in Barrett's esophagus--the good, the bad, and the flawed! - Leedham, S; Jankowski, J (2007)
Gastric acid is believed to be an important etiological factor in the pathogenesis of Barrett's esophagus. Pulsatile acid exposure increases cell proliferation in ex vivo Barrrett's tissue and normalization of esophageal pH reverses this. Proton pump inhibitors (PPIs) are the mainstay of therapy in Barrett's esophagus, and have numerous beneficial effects including symptom control, reduction of inflammation, and promotion of the development of squamous islands. However, PPI therapy causes hypergastrinemia and has not prevented recent increase in the incidences of esophageal cancer. Additionally, evidence presented here by Feagins et al. suggests that acid exposure has a p53-mediated, antiproliferative effect on a nondysplastic Barrett's epithelial cell line, an effect that acid suppression might abrogate. These complex pH, inflammation, and growth factor biological interactions can be most reliably tested in large clinical trials with hard end points like cancer conversion or all causes of mortality. Combining the anti-inflammatory effects of acid suppression with aspirin, a nonsteroidal anti-inflammatory agent, is the subject of the AspECT clinical trial, and this may be the future of chemoprevention in Barrett's.